New trends and challenges for the financial services sector in the Caribbean - Seerattan, Dave ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Reviews the range of financial services available in the Caribbean, the reasons for their increased prominence in the recent past, important trends in the provision of financial services, the determinants of a competitive financial services sector. Suggests some areas in which private players and the monetary authorities may need to take action to help promote the efficiency and stability of this sector.